Imobilização de uma β-galactosidase produzida por Kluyveromyces lactis NRRL Y-1564 cultivada em soro de leite. - Lima, Ariosvana Fernandes (2012)
The enzymatic hydrolysis of lactose by β-galactosidase plays an important role in the processing of dairy products, such as the production of milk containing low concentrations of lactose, the prevention of crystallization in dairy products, and the use of galactosyltransferase for synthesizing galacto-oligosaccharides. In this context, this work aims to study how Kluyveromyces strains can be used to produce β-galactosidase from an agro-industrial by-product such as whey. The species studied were K. marxianus (LAMI CE 025, CCA 510, ATCC 36907) and K. lactis(NRRL Y-1564 and Y-4087). This work also aims to investigate the immobilization of the enzyme onto chitosan and determine its properties such as the optimal operating pH and temperature, the thermal stability of the enzyme, the thermal desnaturation constant, the half-life and the kinetic parameters Km and Vmax using ONPG as substrate of the enzyme β-galactosidase from Kluyveromyces lactis strain NRRL Y1564. K. marxianus LAMI CE 025 and CCA 510 did not consume lactose of the complex medium. The other strains were studied for β-galactosidase production in whey. The maximum enzymatic activity of 3.7 U/mL was achieved by K. lactis NRRL Y-1564 after 12h of fermentation at 180 rpm and 30°C, being selected as a microorganism for β-galactosidase production. The optimal pH for soluble β-gal activity was found to be 6.5 while the optimal pH for immobilized β-gal activity was found to be 7.0, while the optimal operating temperatures were 50°C and 37°C, respectively. The soluble and immobilized enzyme showed similar deactivation profiles at 40°C. For more than 200 min, both biocatalysts showed the same stability, retaining approximately 50 % of their initial activities. However, However, the immobilized enzyme showed an increased stability (8 times) at 50°C. In the lactose hydrolysis at 37°C and pH 7.0 by soluble enzyme was observed a conversion of 58.68% using a enzymatic charge of 2.0 U and 17.57% to 0.5 U. The immobilized enzyme was reused for 10 cycles, showing a good operational stability by retaining more than 74% of its initial activity. The immobilized enzyme retained 100% of its initial activity when it was stored at 4°C and pH 7.0 for a period of 93 days. The soluble β-galactosidase lost 9.4% of its initial activity when it was stored at the same conditions. According to these results, an alternative culture medium prepared by using deproteinized whey supplemented with yeast extract was efficiently used for the production of β-galactosidase through the cultivation of Kluyveromyces strains. Chitosan activated with glutaraldehyde is a suitable alternative low cost support for β-galactosidase immobilization, providing the immobilized enzyme with higher thermal, operational and storage stabilities in comparison with the soluble enzyme.